DEFECTS IN SCIENTIFIC RESEARCH OF THE PROBLEMS OF SPIRITUAL AND MORAL CRISIS AND ITS SOLUTION - Usarov Jabbor Eshbekovich; Eshnayev Nortoji Jumayevich; Haydarova Surayyo Abdusalomovna (International Engineering Journal For Research & Development, 2020)
This article describes how the fields of spirituality and culture can affect human psychology. It also discusses the problems that exist in the system of spirituality and values. In today’s advanced world, people’s mental health depends on its spirituality and value.